PENGUATAN SOSIAL DAN BUDAYA DALAM MENURUNKAN RESIKO BENCANA - Tanzil Tanzil; Tanzil Tanzil (Universitas Halu Oleo (UHO), 2024)
This study aims to analyze social and cultural strengthening in reducing disaster risk. This research took place in Baubau City, Southeast Sulawesi Province. This research uses a qualitative approach with informant retrieval techniques carried out purposively. Informants in this study include community leaders, religious leaders, and those representing the government. The main data collection techniques used are in-depth interviews, observation, and documentation. Data analysis in this study used descriptive-qualitative analysis. The results showed that several disasters that occurred, it has encouraged the community to collectively work together to reduce disaster risk. Social and spiritual capital becomes a force to stimulate collective community action to reduce disaster risk. This illustrates that the community in the research area contains various potentials and strengths and if managed properly will make a positive contribution in reducing disaster risk. For this reason, synergy patterns in reducing disaster risk based on social and spiritual capital must be an important strategy to be developed. This model can encourage the emergence of synergies between NGOs, various community groups, and the government in sustainable disaster management.